2004
DOI: 10.1021/jf049621s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Capacity of Cereal Brans

Abstract: Several oat brans (crunchy oat bran, oat bran alone, and oat breakfast cereal) and wheat brans (wheat bran alone, wheat bran powder, wheat bran with malt flavor, bran breakfast cereal, tablet of bran, and tablet of bran with cellulose) used as dietary fiber supplements by consumers were evaluated as alternative antioxidant sources (i) in the normal human consumer, preventing disease and promoting health, and (ii) in food processing, preserving oxidative alterations. Products containing wheat bran exhibited hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 35 publications
(61 reference statements)
4
64
0
1
Order By: Relevance
“…Sumac sorghum bran was found to have 25 times higher antioxidant capacity than the red wheat bran as measured by the antioxidant ABTS (2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) assay (Awika et al, 2005). Using another antioxidant assay, the TEAC (trolox equivalent antioxidant capacity) assay, wheat bran was shown to have three times the antioxidant capacity than oat bran (Martinez-Tome et al, 2004). Therefore, the antioxidant properties observed here are consistent with those measured by other investigators.…”
Section: Discussionsupporting
confidence: 90%
“…Sumac sorghum bran was found to have 25 times higher antioxidant capacity than the red wheat bran as measured by the antioxidant ABTS (2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) assay (Awika et al, 2005). Using another antioxidant assay, the TEAC (trolox equivalent antioxidant capacity) assay, wheat bran was shown to have three times the antioxidant capacity than oat bran (Martinez-Tome et al, 2004). Therefore, the antioxidant properties observed here are consistent with those measured by other investigators.…”
Section: Discussionsupporting
confidence: 90%
“…In EPR experiments we generate the SO •− 4 with high redox potential, which are capable of reacting with a variety of other compounds present in the extracts (e.g. lignans, polysaccharides, anthocyanins, phytic acid, tannins and flavonoids) other than phenolics (Martínez-Tomé et al 2004). …”
Section: Electron Paramagnetic Resonance (Epr) Studiesmentioning
confidence: 99%
“…On the other hand, cinnamic acid and ferulic acid have been tested for antitumor activity (Nair et al, 1991;Varnavas et al, 1991;Liu et al, 1995;Cardenas et al, 2006) with promising results. Again, obtained from different sources, gentisic acid (Martínez-Tomé et al, 2004), caffeic acid, p-coumaric acid (Sousa et al, 2004), ferulic acid (Anselmi et al, 2004), and cinnamic acid (Mansouri et al, 2005) were shown to possess antioxidant activity.…”
Section: Introductionmentioning
confidence: 98%